Estudo da partição de imunoglobulina G em sistemas aquosos bifásicos utilizando PEG/tampão citrato - Torres, Ana Alice de Fátima Nunes (2013)
In this work, it was studied the extraction of immunoglobulin G (IgG) in Aqueous Two Phase Systems (ATPS) composed of polyethylene glycols (PEG) with molecular weight equal to 4000, 6000 and 8000 g.mol-1 and citrate buffer with pH 5.0, 6.0 and 7.0. First, the behavior for each system in equilibrium was determined by two different methodologies: cloud-point from which binodal curves were obtained and density, which led to the tie-lines. The results obtained by both techniques showed good agreement. It was observed that the increase in PEG molecular weight and the increase in citrate buffer pH led to an increase in the area of the binodal curve. However, for the latter case, the expansion of two-phase region was not significant when the pH increased from 6.0 to 7.0. Regarding the tie-lines, there were also no significant changes in both length and slopes of the same while varying the molecular weight and pH, which shows the high ability of citrate ions on hydrating theirselves preferably and promoting fully or almost fully the PEG exclusion bottom phase, as observed in this study. The study of partition was made from a statistical design of type 24 with complete resolution and adding three central points, having as variables % PEG, % citrate buffer, pH and PEG molar mass. For this purpose the software Statistica 7 was used. 19 experiments were performed and each independent variable was tested in three levels, being the values of PEG percentage equals to 26, 28 and 30% (m/m) and citrate buffer percentage equals to 8, 10 and 12% (w/w). The experiments showed that the highest values of the partition coefficient (Kp) were obtained in systems with pH 7.0 and 12% citrate buffer, classified as statistically significant factors. These values of pH and % citrate buffer were settled and other 27 experiments were conducted with different concentrations of NaCl (0, 0.2 and 0.4 M). There was an increase in the Kp value when the NaCl concentration increased. The results of this study showed that high Kp values can be obtained even at low concentrations of neutral salt. This result is satisfactory since the use of high concentrations of salts in an industrial process may cause various problems such as the reduction in service life due to corrosion of the equipment thereof.